HIGHER EDUCATION CURRICULUM MANAGEMENT SYSTEM - Marija Jovanović; Dragana Dimitrijević (Facta Universitatis. Series, Teaching, Learning and Teacher Education, 2023)
Curriculum management is an important aspect and prerequisite for successful teacher leadership and teaching process quality. In order to ensure horizontal and vertical alignment and the development vision of instruction, it is necessary to identify the functional elements of this dimension in the context of higher education. For these reasons, the concept of curriculum management is viewed in this paper from the perspective of three main functions: monitoring and evaluating the teaching process, coordinating curriculum development, and tracking student progress by university teachers and associates. With the aim of determining whether and to what extent the above-mentioned dimensions of curriculum management are present at the higher education level, the research was conducted on a sample of 216 students from four faculties of the University of Niš. The results of this research show the studied functions a are present at a significant level with a statistically significant frequency of their use among the teaching associates. As for the individual components of the surveyed functions, a statistically significant difference was found between the teachers from different faculties in terms of: teacher evaluation of students' involvement in the instruction process, student motivation for more intense engagement and student involvement in the evaluation process. On the other hand, teaching associates are characterized by different approaches to monitoring and evaluating instruction in terms of checking the level of understanding of the content covered in class. The established differences point to the conclusion that the researched functions are more effectively realized at faculties where instruction happens in smaller groups and where the functional learning objectives are emphasized. From the standpoint of legislation and standards for the accreditation of study programs, it can be concluded that they provide a favorable foundation for curriculum management, and that by mapping shortcomings and strategic planning of future activities, this field can be significantly improved.